2010
DOI: 10.1007/s11090-010-9251-6
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Montmorillonite-Graft-Acrylic Acid Superabsorbent by Using Glow-Discharge Electrolysis Plasma

Abstract: Crosslinking graft polymerization of poly acrylic/montmorillonite superabsorbent composite in aqueous solution was prepared by using glow-discharge electrolysis plasma, in which acrylic acid and acid-activated montmorillonite were used as starting materials, N,N-methylenebisacrylamide as a crosslinking agent. To optimize the synthetic conditions, seven important parameters of the graft-polymerization were examined in detail, such as the discharge voltage, discharge time, the neutralization of acrylic acid, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Consequently, absorbency decreased. In addition, excessive MMT particles might physically filled in the polymeric network, causing separation of MMT from P(AA-co-AMPS) copolymer and shrinkage of the composite, 23 thus, the absorbency decreased accordingly.…”
mentioning
confidence: 99%
“…Consequently, absorbency decreased. In addition, excessive MMT particles might physically filled in the polymeric network, causing separation of MMT from P(AA-co-AMPS) copolymer and shrinkage of the composite, 23 thus, the absorbency decreased accordingly.…”
mentioning
confidence: 99%
“…FT-IR spectra of (a) reed hemicellulose and (b) temperature/pH dual sensitivity reed hemicellulose-based hydrogels (The discharge voltage and discharge time was 600 V and 90 s, respectively). CH(CH 3 ) 2 contraction vibration absorption peak (Peng et al, 2011(Peng et al, , 2012Gao et al, 2010). These suggested that the COOH group in the acrylic acid (AA) and hydrophilic groups ( CONH 2 ), hydrophobic isopropyl ( CH(CH 3 ) 2 ) in N-propyl acrylamide (NIPAAm) had been copolymerized with hemicellulose and successfully introduced into the structure of the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…At higher discharge voltage, short chains of molecules were apt to form, as well as monomers were easy to self-crosslinking and implosion, which resulted in the decrease of molecular weight and failure of forming effective space structure. In addition, higher discharge voltage facilitated the degradation of its own network also led to destruction of network structure and lower swelling ratio (Gao et al, 2008(Gao et al, , 2010Lu, Yu, Gao, Yang, & Li, 2011).…”
Section: Morphology Of Temperature/ph Dual Sensitivity Reed Hemicellumentioning
confidence: 99%
“…10 This large market evokes a strong desire to develop novel SAPs materials with higher water absorbency and excellent mechanical properties. In recent years, polysaccharide-based, 11 graphene oxide (GO)-based 12 and acrylic acid (AA)-based SAPs [13][14][15][16][17][18][19][20][21][22][23][24][25] have become ubiquitous and indispensable materials. Poly(acrylic acid) (PAA) hydrogels, in particular, dominate the market because of their low price and simple synthesis process.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, many efforts have been made to improve these performances of PAA-based hydrogels, such as exploiting composite hydrogels including inorganic clay materials, [13][14][15][16][17][18] graphene oxide, 19,20 chitosan, 21,22 silk sericin, 23 maize bran, 24 and designing double-network hydrogels. 25 For example, Li et al 21 reported a dynamic cross-linked network via in situ polymerization of AA and acrylamide (AM) monomers in the aqueous solution of chitosan.…”
Section: Introductionmentioning
confidence: 99%